3 - Manioc, rente foncière et situation des femmes dans les environs de «Kpove- Village» en pays Ouatchi: by Ewihn-Liba Pana - Ewihn-Liba Pana (Africa Development, 1995)
Cassava cultivation is widespread in Ouatchiland, in the south-eastern part of Togo. This study is an inquiry into the conditions under which cassava is produced and processed for use by the people taking account cf the seasonal cycles applying to cassava production It is realised that cassava production cawtot be considered out of the social environment that supports iL The study shows that the role of Ouatchi women in agriculture is growing thereby giving rise to conflictual social relations in the society at large As an example cf gender analysis integration, the study contributes to developing the knowledge about women in the Togolese society.